Frequency of human leukocyte antigen (hla) in patients with malaria and in the general population of Humaitá county, Amazonas state, Brazil - Domingos Alves Meira; Jordão Pellegrino Júnior; Jussara Marcondes-Machado; Kimiyoski Tsuji; Elinda Satie Matsuoka; Elizete Haida; Albert Boutros El Khoury (Sociedade Brasileira de Medicina Tropical (SBMT), 1987)
In August 1983,85 inhabitants of the municipality of Humaitá, Amazonas State, Brazil were studied to determine the prevalence of antigens to HLA-A, -B, -C and DR. Thirty-eight were sick with malaria due to Plasmodium falciparum. All subjects were examined for splenomegaly, blood parasitaemia and antibodies to malaria. They constituted three groups: 1) 25 subjects native to the Amazon region who had never had malaria; 2) 38 Amazonian subjects who had malaria in the past or currently had an infection; 3) 22 patients with malaria who had acquired the infection in the Amazon Region but came from other regions of Brazil. Blood was taken from each person, the lymphocytes were separated and typed by the test of microlymphocytotoxicity. There was a high frequency of antigens that could not be identified in the groups studied which suggests the existence of a homozygote or phenotype not identified in the population. There was a high frequency of the phenotype Ag(W24) (44.7%) in group 2 when compared with group 1 (32%) or group 3 (9%). Also the individuals in group 2 showed an elevated frequency of antigen DR(4)80%) when compared with group 1 (36.6%) or group 3 (16.6%). These observations suggest the possibility of a genetic susceptibility to malaria among Amazonian residents and indicate a necessity for more extensive studies of the frequency of HLA antigens among inhabitants of this endemic malarial zone. Em agosto de 1983 foram observados 85 habitantes do Município de Humaitá, Estado do Amazonas, Brasil, com a finalidade de estudar a prevalência dos antígenos de HLA -A, -B, -C e DR, dentre os quais 38 eram doentes com malária causada pelo Plasmodium falciparum Todos eles foram examinados para avaliação de esplenomegalia, exame parasitológico de sangue e pesquisa de anticorpos de malária. Foram constituídos três grupos: (I) 25 indivíduos nascidos na região Amazônica que nunca tiveram malária; (II) 38 indivíduos naturais da Amazônia que tinham sido tratados de malária no passado, ou que estavam tendo malária atual, e ...